STRESS AND STRENGTH ANALYSIS RANGKA OF CC DH LOCOMOTIVE BOGIES FRAME AND RELATED WITH FAILURE IN KRDI MOTOR BOGIES FRAME - BAGASKORO (NIM : 13106123); Tim Pembimbing : Prof. Dr. Ir. Mardjono Siswosuwarno; Prof. Dr. , WIRIO
In 2010 PT INKA Madiun have started the first project production of locomotive diesel hydraulic Co-Co (CC DH) in Indonesia. The author got the opportunity to join internship programe in this project at the engineering division of PT INKA. The authors main job in this project as a team in analysis and verification of CC DH locomotive bogies frame structure static strength using the finite element method software ANSYS 11. Analysis started with calculation of loads on the bogie frame structure, the loads is applied according to the case load which refers to the standard, until obtain the value and position of maximum stress on the gearbox mounting connection from the analysis and calculation using ANSYS 11. The value of maximum stress used in an equation for estimating the fatigue life and the operation time of the gearbox mounting connection if cold crack is assumed to occur along a millimeter. The author of this final discussion focuses on the strength analysis of the gearbox mounting connection CC DH locomotive bogies frame, due in May 2010 in cases of failure in the gearbox mounting connection KRDI motor bogies frame. The results from the calculation of fatigue life estimation and operation time of the gearbox mounting connection is very short time (+ 4 months). This is caused the value of maximum stress is too high, that occurs from the calculation of the vertical load on the gearbox mounting connection with multiplier factor of 20. From the iteration results obtained multiplier factor of 10.2 for the gearbox mounting connection CC DH locomotive bogies frame, that results is approaching the fatigue life of the gearbox mounting connection KRDI motor bogies frame.